PERMASALAHAN TOKOH UTAMA DALAM NOVEL ORANG-ORANG BIASA KARYA ANDREA HIRATA : KAJIAN SOSIOLOGI SASTRA - Chaterina Noya (Prosiding Seminar Nasional Sasindo, 2022)
This study aims to describe the form of economic, cultural, biological, and psychological problems against the main character in Andrea Hirata's novel Orang-orang Biasa. The theory used is Soerjono Soekanto's social problem. The research method used is descriptive analysis method which is carried out by describing the facts followed by analysis of the data used as the object of research. The data used are excerpts of dialogue and sentences taken in the novel Orangorang Biasa by Andrea Hirata. The data collection technique used is a literature study technique followed by note-taking techniques and data analysis techniques. Based on the findings of social, economic, and educational problems in the novel Orang-orang Biasa by Andrea Hirata, 30 data were analyzed. The results of the study are then divided into several parts. The first part is the economic problem which consists of 13 data, then the cultural problem consists of 7 data, the biological problem consists of 4 data, and the psychological problem consists of 3 data. Based on the results of the research that has been divided into several parts, it can be seen that economic problems are the center of the problem for the main character in the novel Orang-orang Biasa by Andrea Hirata.Kata Kunci/Keywords: social problem, literary sociology, novel